Literature Review: Perilaku Perawatan Kesehatan Gigi Orang Tua Bagian dari Promosi Kesehatan Anak Usia Dini - Olinne Juzika (Pelantar Press, 2026)
Oral and dental health problems in early childhood remain a major public health concern worldwide, including in Indonesia. Early Childhood Caries (ECC) is one of the most common oral health problems among preschool children and may negatively affect quality of life and child development. Preventive efforts to address oral health problems in early childhood cannot be separated from the role of parents, as children are highly dependent on parental guidance in forming daily health behaviors. Parental oral health care behaviors, such as supervising toothbrushing, regulating the consumption of cariogenic foods, and utilizing dental health services, represent an essential component of family-based health promotion strategies. This review aims to analyze parental oral health care behaviors as part of health promotion efforts for early childhood based on studies published between 2020 and 2025. A narrative literature review approach was applied by searching scientific articles through Google Scholar, PubMed, and DOAJ databases. Included articles focused on parental roles, knowledge, and behaviors related to early childhood oral health care and their contribution to the prevention of oral health problems. The findings indicate that parental oral health care behaviors are significantly associated with early childhood oral health status. Parents with higher levels of knowledge and health literacy tend to implement more consistent and preventive oral health practices for their children. In addition, health promotion interventions involving parents have been shown to be effective in improving children’s oral health behaviors and reducing the risk of oral health problems. This review concludes that parental oral health care behavior is a key component of early childhood health promotion and should be strengthened through sustainable family-based education and empowerment strategies